PENGARUH RENDAM KAKI DENGAN AIR HANGAT TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH SP 4 SETUNTUNG KECAMATAN BELITANG KABUPATEN SEKADAU - Nurpratiwi Nurpratiwi; Elveni Novari (Sekolah Tinggi Pariwisata Mataram, 2021)
Hypertension is a factor that often gives effect to the occurrence of heart disease and blood vessels. Hypertension often does not cause symptoms in the initial phase, but hypertension will disrupt the function of the heart even the patient will have a stroke. In addition to pharmacological therapy, the management of hypertension can use non-pharmacological therapy one of them therapy warm water foot soak. The aim of this research is to know the influence of foot soak with warm water to blood pressure of hypertension patient of Sp 4 Setuntung. This study uses a quantitative approach. The method used is quasi experiment. The design of this research is pre and post test without control. Sampling technique used is Purposive sampling. Respondents in this study as many as 17 people. The result based on Wilcoxon test on systole blood pressure before and after get p value of systole 0.001 (<0.05) and for diastole blood pressure p value of diastole 0.048 (<0.05). The conclusion of this study foot soak therapy with warm water effectively lower blood pressure in patients with hypertension in the region Sp 4 Setuntung Kecamatan Belitang Kabupaten Sekadau.